Pemenuhan Kebutuhan Pemustaka Terhadap Koleksi Perpustakaan Di Dinas Kearsipan Dan Perpustakaan Kabupaten Bener Meriah - Novita Sari; Achiriah Achiriah; Franindya Purwaningtyas (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study aims to determine the fulfillment of the needs of user collections and to find out the obstacles faced in meeting the needs of users. The research method used is a qualitative method with descriptive research that uses interviews to describe data obtained by researchers directly from informants. Some of the data collection techniques carried out in this study are observation, interviews, and documentation. Furthermore, researchers conducted interviews with 4 informants, namely the Head of the Archives and Library Office of Bener Maeriah Regency, the Head of the Library Section, and 2 visiting users. The results of the research revealed that in fulfilling the needs of users of library collections, the Archives Office and the district library were actually busy carrying out several activities, namely the selection of library materials, the procurement of library materials, and the care of library materials. However, in meeting the needs of users, namely library collections are constrained by a very minimal budget, inadequate collections, human resources and limited time access, thus affecting the fulfillment of user needs to meet the needs of users.